Athletes` protection from concussion in different Olympic combat sports. Let`s start from the rules - Arriaza, R.; Martínez de Quel, O.; Gómez, M.; Augustovicova, D. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: In the past decade, sports-related concussions have drawn considerable attention from the public, the media, and sports medicine professionals. Epidemiological reports provide convincing evidence that numerous concussions occur at all levels of sport activity, but little is known about the differences in the level of protection that rules offer to the athletes in different sports, especially in those where risks are higher, as combat sports.